2013
DOI: 10.1021/jp407801u
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Water Content on Conversion of d-Cellobiose into 5-Hydroxymethyl-2-furaldehyde in a Dimethyl Sulfoxide–Water Mixture

Abstract: Noncatalytic conversion of D-cellobiose (at 0.5 M) into 5-hydroxymethyl-2-furaldehyde (5-HMF), a platform chemical for fuels and synthetic materials, was analyzed at 120-200 °C over a wide range of water mole fraction, xw = 0.007-1 in a binary dimethyl sulfoxide (DMSO)-water mixture by means of the in situ (13)C NMR spectroscopy. Effects of the water content were revealed as follows: (i) The tautomerization of the anomeric residue of D-cellobiose from D-glucose to D-fructose type was not initially observed at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(44 citation statements)
references
References 46 publications
3
41
0
Order By: Relevance
“…Disaccharides (sucrose [29] and cellobiose [30] ), polysaccharides (inulin [31] ), and even cellulose itself [32] can be used as starting materials, the latter after depolymerization. Disaccharides (sucrose [29] and cellobiose [30] ), polysaccharides (inulin [31] ), and even cellulose itself [32] can be used as starting materials, the latter after depolymerization.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Disaccharides (sucrose [29] and cellobiose [30] ), polysaccharides (inulin [31] ), and even cellulose itself [32] can be used as starting materials, the latter after depolymerization. Disaccharides (sucrose [29] and cellobiose [30] ), polysaccharides (inulin [31] ), and even cellulose itself [32] can be used as starting materials, the latter after depolymerization.…”
Section: Resultsmentioning
confidence: 99%
“…Disaccharides (sucrose [29] and cellobiose [30] ), polysaccharides (inulin [31] ), and even cellulose itself [32] can be used as starting materials, the latter after depolymerization. Extensive research is currently underway to develop efficient, cheap, and sustainable commercial methods for the preparation of 5-HMF.…”
Section: Resultsmentioning
confidence: 99%
“…The best-performing covered catalyst, namely Ru/CB@SiO 2 (P), was finally tested in a model reaction of cellulose valorization: the catalytic transformation of cellobiose into sorbitol in one pot. Kinetic modeling has shown that hydrolysis is the rate-limiting step for the hydrolytic hydrogenation of cellobiose (or cellulose) to sorbitol (110-115 KJ/mol for the hydrolysis of cellobiose) [19,40]. Therefore, this step is a highly demanding reaction that usually requires strong acid sites irrespective of the reaction pathway to produce sorbitol, as shown in Figure 4.…”
Section: Catalytic Testsmentioning
confidence: 99%
“…For instance, Mellmer et al have shown that the rate of cellobiose hydrolysis is strongly improved by using γ-valerolactone as solvent compared to conversion in aqueous media [18]. More recently, it has been proven that by tuning the water content in dimethyl sulfoxide, as well as the temperature and the reaction time, it is possible to perform a non-catalytic conversion of cellobiose into 5-hydroxymethyl-2-furaldehyde [19]. In addition to the solvent nature in which the catalytic reaction is carried out, it has been also proven that the mesoporous silica material type, and indirectly some parameters such as the wall thickness, have a great influence on the material hydrothermal stability [7].…”
Section: Introductionmentioning
confidence: 99%
“…So far, it is well known that some polar aprotic solvents like dimethyl sulfoxide (DMSO), N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMA), and 1,4-dioxane are the most favourite solvents for the dehydration of fructose because they have considerable solubility to fructose and can inhibit the decomposition of 5-HMF to levulinic acid as occurred in the presence of water and other protic solvents. 5,[7][8][9] The application of imidazolium-based ionic liquids and other deep eutectic mixtures as dual acid catalyst and solvent may be the most effective strategy for the dehydration of fructose as well as other carbohydrates. 4,[10][11][12] However, their high boiling points and excellent miscibility with 5-HMF bring a huge challenge to the post-separation of 5-HMF from the reaction bulk, which seems less feasible for industrialization even though much progress has been made in the separation of 5-HMF from ionic liquids.…”
mentioning
confidence: 99%